Oral hygiene in stroke survivors undergoing rehabilitation: does upper extremity motor function matters?. Issue 7 (3rd October 2021) - Lawal, IU; Ibrahim, R; Ramphoma, KJ
ABSTRACT: Background : Traditionally, stroke rehabilitation outcomes are based on indicators of physical function, such measures may underrate the all-inclusive impact of stroke such as oral health.Objectives : To investigate the relationship between upper extremity motor function and oral hygiene status as well as the impact of stroke on Oral Health-Related Quality of Life (OHRQoL).Methods : Sixty stroke survivors were included in this cross-sectional survey. Spasticity and motor function/mobility of the affected upper extremity were assessed using the Modified Ashworth Scale and Action Research Arm Test, respectively. Oral hygiene was assessed using the Simplified Oral Hygiene Index and oral health impact was assessed using the 14-item Oral Health Impact Profile. Pearson's moment correlation coefficient was used to determine the relationship between oral hygiene and upper extremity motor function variables.Results : There were significant relationships between the oral hygiene index and Shoulder muscles spasticity (r = 0.374, p = .01), wrist muscles spasticity (r = 0.352, p = .01), as well as basic mobility (r = 0.423, p = .01). An estimated 8% (n = 5) of study participants have their QoL strongly impacted by their oral health.Conclusions : Upper extremity motor function variables such as spasticity and basic mobility matters in determining oral hygiene status after stroke. Stroke has little impact on oral health-related quality of life.